PENGARUH LAYANAN INFORMASI TENTANG WIRAUSAHA TERHADAP MOTIVASI BERWIRAUSAHA PESERTA DIDIK KELAS XI SMAN 8 - Ramadhani, Suci; Astuti, Indri; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the influence of information services about entrepreneurship on entrepreneurship motivation in students class XI SMA Negeri 8 Pontianak. The method used is descriptive method with quantitative approach. The sample in this research is 51 students of class VIII. Technique of collecting data in this research is indirect communication technique with data collection tool that is kuesioner. Data analysis technique used is the percentage formula, product moment analysis and coefficient of determination. The result of data analysis shows that information service about the entrepreneur given by the supervising teacher on the students of grade XI SMA Negeri 8 Pontianak reaches 91% is the